Peningkatan Kemampuan Bernyanyi Siswa Secara Unisono Menggunakan Metode Tutor Sebaya Di Kelas VII.1 SMPN 6 Sijunjung - Kemri Firdana; Ardipal Ardipal (FBS Universitas Negeri Padang, 2020)
This study aims to findstudents improvements in learning to sing local folk songs in unison singing through peer tutor method in class VII.1 at SMP Negeri 6 Sijunjung. This research was conducted in March-July 2020. The research subjects were 30 studentsof class VII.1 at SMP Negeri 6 Sijunjung. This study applied peer tutor method in learning music in unisono singing and wasconducted in two cycles. Each cycle consisted of 2 meetings. The 2 meetings consisted of four stages: planning, implementing actions, observing, reflecting, and evaluating. The data were collected through field notes, observations, performance tests, and interviews. The data analysis conducted was the result of implementing the actions taken. The results show that there is an improvement in unisonosinging ability by using peer tutor method forstudents in class VII.1 at SMP Negeri 6 Sijunjung. This improvement can be seen in the quality of the process shown through students’enthusiasm and activeness in learning music.The improvement in the result quality can be seen from the increase in score and average before and after the implementation. The average value before implementation is 44.12. In the first cycle the average value increases to 70.03, and in the second cycle it increases to 84.19.The average from pre-action to cycle II has increased by 40.07 and has met the Minimum Completion Criteria which is 75. From the above research, it is known that peer tutor method succeeds in improving student learning outcomes in singing local folk songs in class VII.1 at SMP Negeri 6 Sijunjung.